Inversion of Nonhyperbolic P-wave Traveltimes for Interval Transverse Isotropy Parameters - Asgharzadeh, M.; Nadri, D.; Bona, Andrej (2015)
In this study, we analyse the accuracy of layer-stripping method to use P-wave reflection traveltimes in transverse isotropic media with vertical axis of symmetry (VTI) to estimate interval anisotropic parameters that are required for seismic processing. We also present a synthetic Walkaway VSP example in which a comparison can be made between the results of layer-stripping method and conventional method of using P-wave slownesses measured in a borehole. In the error analysis part, we quantify the errors of estimating interval Thomsen parameters, Epsilon and Delta for a horizontal VTI layer underneath a VTI overburden using noise free traveltimes computed by anisotropic ray tracing. Our analysis shows that both the parameters can be well constrained using traveltimes corresponding to maximum offset to depth ratio equal to 1 and overburden anisotropy plays no significant role in the accuracy of the inversions. On the other hand, parameter estimation using synthetic VSP data shows that an accurate and stable inversion requires traveltimes taken from spreads with maximum offset to depth ratio equal to 1.4 for Delta estimation and 4 for Epsilon estimation. The presented layer stripping-method also compares well with slowness based inversion using VSP data.